Express cos(2x) in terms of acos^2(x) + b

cos(2x)=cos2(x) - sin2(x)use sin2(x) = 1 - cos2(x)so cos(2x)=cos2(x) - (1 - cos2(x))cos(2x)=2cos2(x) - 1so a = 2 and b = -1

Related Maths A Level answers

All answers ▸

given that angles A and B are such that, sec^2A-tanA = 13 and sinBsec^2B=27cosBcosec^2B


How to prove that (from i=0 to n)Σi^2= (n/6)(n+1)(2n+1), by induction.


Given that y > 0, find ∫((3y - 4)/y(3y + 2)) dy (taken from the Edexcel C4 2016 paper)


If y = 2^x, solve the equation 8(4^x) + 9(2^x) + 1 = 0 in terms of y.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences